Quantification of household electricity consumption for supporting energy efficiency of urban metabolism: Material flow analysis - Sharif Ali, Sharif Shofirun; Kasavan, Saraswathy; Razman, Muhammad Rizal; Awang, Azahan; Zarco-Periñán, Pedro J. (International Journal of Renewable Energy Development, 2024)
Despite growing public, academic, and government awareness of the energy consumption issue, there is still little research on the scales and patterns of Household Electricity Consumption (HEC), particularly in developing countries such as Malaysia. Therefore, the present study examines the status of HEC using electricity consumption breakdowns, key performance indicators (KPIs) for electricity consumption and Material Flow Analysis (MFA) by showing potential electricity savings, cost savings, and emission reductions using 5-star energy efficiency appliances. This study used a face-to-face survey of 400 participants in Seremban, the capital city of Negeri Sembilan. The study found that the majority of respondents (49%) consumed about 300-600 kWh/month of electricity with an estimated cost of MYR231.80 per month. Additionally, the study found that households in flats recorded lower average electricity consumption (460.16 kWh/unit) than bungalow households (885.92 kWh/unit) due to respondents’ socio-economic status, the physical size of the houses and the number of appliances owned. The study also revealed that the average energy consumption was higher for refrigerators (9.6 kWh/day) and air conditioners (4.5 kWh/day) due to the use of large amounts of energy to maintain a steady temperature. The material flow analysis shows that energy savings were approximately 22.53%, potential cost savings were MYR12,676.15 per month, and the potential reduction emissions were about 100,759.92 kgCO2e for one month with using EEA compared to non-EEA. The present study empirically discussed the significance of HEC quantification and the opportunity for energy efficiency is critical as a solution for sustainable urban metabolism in a developing country.